2009
DOI: 10.4166/kjg.2009.53.5.283
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Multicenter Study on the Prevalence and Symptoms of Erosive Reflux Esophagitis in Secondary and Tertiary Hospitals in Korea

Abstract: The prevalence of EE among outpatients visiting gastroenterology clinics in Korea was 11.8%. Independent factors associated with increased prevalence of EE were males irrespective of age, old aged (> or =65 years) females, number of typical GERD symptoms, and frequent typical GERD symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…It is clear that endoscopy is the only method of investigation to make a diagnosis of erosive esophagitis and grading its severity. According to a recent report, prevalence of erosive esophagitis in secondary and tertiary hospitals in Korea was 11.8% 20. In the present study, prevalence of erosive esophagitis by EGD in type II DM patients was 18.9%.…”
Section: Discussionsupporting
confidence: 49%
“…It is clear that endoscopy is the only method of investigation to make a diagnosis of erosive esophagitis and grading its severity. According to a recent report, prevalence of erosive esophagitis in secondary and tertiary hospitals in Korea was 11.8% 20. In the present study, prevalence of erosive esophagitis by EGD in type II DM patients was 18.9%.…”
Section: Discussionsupporting
confidence: 49%
“…The term heartburn is less well understood in Asia. A previous Korean study has reported that the most common presenting symptom in patients with reflux esophagitis is epigastric pain or discomfort and that acid regurgitation is more prevalent than heartburn [44].…”
Section: Discussionmentioning
confidence: 99%
“…The severities of reflux related symptoms (heartburn, acid regurgitation, chest discomfort, chest pain, hoarseness, globus sensation, cough, epigastric pain, epigastric soreness and dyspepsia)10 were recorded by 10 cm VAS running from 0 (no symptom) to 10 (maximal symptom expression).…”
Section: Methodsmentioning
confidence: 99%